Clinical and microbiological effects of photodynamic therapy applied in non-surgical treatment of periodontitis - Arsić, Zoran; Jovanović, Radovan; Djordjević, Aleksandar; Šehalić, Meliha; Marjanović, Dragan; Mikić, Mirko; Vlahović, Zoran; Mladenović, Raša (Vojnosanitetski pregled, 2022)
Background/Aim. Treatment of periodontitis undergoes several treatment phases. Non-surgical periodontal treatment (NSPT) represents the basic treatment stage, and it is applied to all the patients undergoing periodontal treatment. Adjunctive antimicrobial photodynamic therapy (aPDT) is one of several contemporary and relatively new possibilities with a role to inactivate microorganisms responsible for the occurrence and progression of the disease. The aim of this study was to comparatively analyze the clinical and microbiological effects of the NSPT alone, as well as combined with aPDT. Methods. A split-mouth method design was used in a prospective randomized controlled trial. The following clinical parameters were registered and monitored: plaque index (PI), bleeding on probing, probing depth (PD), and clinical attachment level (CAL). The presence of microorganisms Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, and Treponema denticola was detected by the polymerase chain reaction (PCR) method. Samples were tested before the therapy, as well as three months after the therapy. Therapeutic modalities of NSPT and NSPT with adjunct aPDT were examined. Results. All of the analyzed clinical parameters proved statistically significant improvement after the application of both treatment modalities (p < 0.001). Microbiological analyses showed that the total number of microorganisms was statistically significantly lower after the application of both methods (p < 0.001). Following the treatment, there was a statistically significantly reduced number of microorganisms Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, and Treponema denticola (p < 0.001). NSPT combined with aPDT led to a statistically significant improvement of both clinical parameters and microbiological status compared to NSPT applied on its own. Conclusion. The study showed improvement of all clinical indicators after the application of both treatment modalities. The total number of microorganisms was reduced as well as the number of specific microorganisms. Combining aPDT with NSPT led to a statistically significantly higher reduction in the number of microorganisms compared to NSPT alone.
Keywords: aggregatibacter actinomyctemcomitans; periodontitis; photochemotherapy; polymerase chain reaction; porphyromonas gingivalis; treponema denticola; treatment outcome